Comparison of accelerometry stride time calculation methods - Norris, M.; Kenny, I. C.; Alderson, R. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of this study was to investigate how a newly proposed method of stride time calculation, utilising data filtered at 2 Hz, compared to previous methods. Tibial accelerometry data for 6 participants completing half marathon running training were collected. One run was selected for each participant at random, from which five consecutive running strides were ascertained. Four calculation methods were employed to derive each stride time and results were compared. No significant difference was found between methods (p=1.00). The absolute difference in stride time, when comparing the proposed method to previous methods, ranged from 0.000 seconds to 0.039 seconds. Filtered data could offer a simplified technique for stride time output during running gait analysis, particularly when applied during automated data processing for large data sets.